Effectiveness-efficiency nexus in municipal solid waste management: A non-parametric evidence-based study - Corrado lo Storto (Elsevier, 2021)
The scope of this work is to present a comprehensive approach to analyze the effectiveness-efficiency nexus in the evaluation of the performance of municipal solid waste (MSW) management. The rate of separate MSW collection is used to measure service effectiveness. A multiple set of non-parametric indicators is employed to obtain measurements of technical, scale and congestion efficiencies of waste service provision. This approach was implemented to conduct an empirical study to evaluate the performance of MSW management in 258 municipalities in the Apulia region (Southern Italy) from 2010 to 2017. The study was organized in two phases. In the first phase, measures for the three efficiency indicators were calculated applying Data Envelopment Analysis (DEA) with an output-oriented model specification. In the second phase, Panel Tobit analysis with random parameters was employed to examine the effectiveness-efficiency one way nexus, considering both municipalities’ heterogeneities and context-specific variables. The efficiency analysis shows that several municipalities are still far from achieving acceptable performance scores. Between 2010 and 2017 the average rate of separate MSW collection increased only from 16.6% to 39.6%, while the average loss of technical efficiency ranged from 27% to 39%. On average, such inefficiency was due to an important extent to the low pure technical efficiency that ranged from about 69% to 81%, and to a lesser extent to scale and congestion inefficiencies. Indeed, scale efficiency was between 85.4% and 92.6%, whereas congestion efficiency was higher than 99%. The study also highlights that there is no trade-off between effectiveness and efficiency. For the largest part of the municipalities, high levels of effectiveness and efficiency can be achieved at the same time. For about 83% of the municipalities the decrease of the sorted waste collection rate is associated to a decrease of the pure technical efficiency. A drop of the output congestion efficiency due to a relatively high collection of the unsorted fraction of waste reduces the rate of the sorted waste collection for most of municipalities (77.3%). Results also indicate that for many municipalities (about 87%) improving the MSW service effectiveness necessarily requires reducing the average quantity of waste generated by people.